2021
DOI: 10.1021/acssynbio.1c00175
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Surface Display for In Vitro Biosynthetic Pathway Reconstruction

Abstract: The enzymes immobilized through yeast surface display (YSD) can be used in in vitro metabolic pathway reconstruction as alternatives to the enzymes isolated or purified through conventional biochemistry methods. They can be easily prepared by growing and collecting yeast cells harboring display constructs. This may provide an economical method for enriching certain enzymes for biochemistry characterization and application. Herein, we took the advantage of one-pot cascade reactions catalyzed by YSD-immobilized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 50 publications
(91 reference statements)
0
7
0
Order By: Relevance
“…Many previous studies have demonstrated that the overexpression of the key enzymes involved in the MVA pathway could increase the yields of heterologous triterpenoids in yeast, and the down-regulation of 2,3-oxidosqualene metabolic flux towards ergosterol could redirect more metabolic flux towards the biosynthetic pathways of triterpenoids. 44,45 In order to further increase the production of PPD, we integrated IDI1 , ERG20 , ERG9, ERG1 and antisense ERG7 genes into the δ4 site of strain YP-3, resulting in strain YPU. After being cultivated for 6 d, the titer of PPD in YPU reached 93.1 mg L −1 , which was 2.2-fold that in YP-3 (42.4 mg L −1 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many previous studies have demonstrated that the overexpression of the key enzymes involved in the MVA pathway could increase the yields of heterologous triterpenoids in yeast, and the down-regulation of 2,3-oxidosqualene metabolic flux towards ergosterol could redirect more metabolic flux towards the biosynthetic pathways of triterpenoids. 44,45 In order to further increase the production of PPD, we integrated IDI1 , ERG20 , ERG9, ERG1 and antisense ERG7 genes into the δ4 site of strain YP-3, resulting in strain YPU. After being cultivated for 6 d, the titer of PPD in YPU reached 93.1 mg L −1 , which was 2.2-fold that in YP-3 (42.4 mg L −1 ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Green Chemistry flux towards ergosterol could redirect more metabolic flux towards the biosynthetic pathways of triterpenoids. 44,45 In order to further increase the production of PPD, we integrated IDI1, ERG20, ERG9, ERG1 and antisense ERG7 genes into the δ4 site of strain YP-3, resulting in strain YPU. After being cultivated for 6 d, the titer of PPD in YPU reached 93.1 mg L −1 , which was 2.2-fold that in YP-3 (42.4 mg L −1 ) (Fig.…”
Section: Papermentioning
confidence: 99%
“…However, preparation processes such as enzyme purification and matrix selection for immobilization are usually time-consuming and expensive [ 46 ]. The microbial surface-displayed strategy of fusing target enzymes with cell wall carrier proteins avoids laborious, time-consuming processes of immobilization [ 47 , 48 ]. Here, the CarCby whole cell biocatalyst presented a potential candidate for the biodegradation of carbaryl, a kind of carbamate pesticide.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, the host cells for surface display are mainly concentrated in phage, bacteria, yeast, , and Bacillus subtilis spores. However, any traditional cell surface display system has shortcomings. The molecular weight of the polypeptide or protein displayed on the phage cannot be too large; otherwise, it will affect the assembly and infection of the phage.…”
Section: Introductionmentioning
confidence: 99%